Design and construction of a press tool for making plastic paving blocks - Usman, Usman; Syukran, Syukran; Armansyah, Agus (Journal of Mechafa Engineering and Fabrication, 2024)
Paving block industries have emerged in the North Aceh Regency area, especially for the Baktiya District area where there are 7 paving block industries, which is due to the increasing demand for paving blocks of 1000 units per day in 2019 for office yards, parking lots, for pedestrian sidewalks and for parks. The compressive strength that can be accepted by paving blocks with PET plastic shredded substitution for each composition is as follows, in normal paving blocks (0%) of 11.32 MPa, in paving blocks with an addition of 0.3% of 12.31 MPa, in paving blocks with an addition of 0.4% of 12.70 MPa, in paving blocks with an addition of 0.5% of 14.55 MPa, and in paving blocks with an addition of 0.6% of 11.82 MPa. The percentage of the ability of paving blocks with PET plastic shredded substitution for each composition in absorbing water is as follows, in normal paving blocks (0%) it is 10%, in paving blocks with the addition of 0.3% it is 8%, in paving blocks with the addition of 0.4% it is 7%, in paving blocks with the addition of 0.5% it is 5%, and in paving blocks with the addition of 0.6% it is 9% Mpa